Controllable Generation of Antiferromagnetic Skyrmions in Synthetic Antiferromagnets with Thermal Effect. (18th January 2022) - Chen, Ruyi; Cui, Qirui; Han, Lei; Xue, Xiaotian; Liang, Jinghua; Bai, Hua; Zhou, Yongjian; Pan, Feng; Yang, Hongxin; Song, Cheng
Abstract: Magnetic skyrmions have gained unprecedented attention for their potential applications in spintronic devices, such as non‐volatile memory, energy‐efficient, and non‐von Neumann devices. In particular, skyrmions in synthetic antiferromagnets (SAF) are believed to overcome the fundamental limitations of the widely studied ferromagnetic skyrmions in terms of size and effective current‐induced manipulation. Recently, several methods have been proposed to stabilize SAF skyrmions, however, the controllable creation and manipulation of skyrmions in SAF remains a challenge. Here, the generation, manipulation, and current‐driven dynamics of SAF skyrmions are studied by a thermal induced integrated device. The thermal created SAF skyrmion provides a prerequisite for the subsequent current‐driven dynamics research where apparent inhibition of skyrmion Hall effect is observed due to the effectively compensated topological charge. In addition, by tuning the heating current, the density of skyrmions in SAF can be effectively manipulated, which is a key factor for utilizing SAF skyrmions toward practical spintronic devices. Abstract : The generation, manipulation, and current‐driven dynamics of synthetic antiferromagnetic skyrmions in Pt/[Co/Pd]/Ir/Pt/[Co/Pd]/Ir multilayers are realized by a thermal induced integrated device. The controllable density of skyrmions by tuning the heating current and the inhibition of skyrmion Hall effect during applying current pulses in synthetic antiferromagnet show promise for putting skyrmions into practical applications.